Intrarenal renin-angiotensin system activation and urinary angiotensinogen as a novel biomarker of nephropathy in childhood - Urushihara, Maki (Japanese journal of pediatric nephrology, 2012)
Intrarenal renin-angiotensin system activation plays a pivotal role in the pathogenesis of hypertension and chronic kidney disease. Recently, the focus of interest in the renin-angiotensin system has shifted toward the role of the local/tissue renin-angiotensin system in specific tissues. Angiotensinogen is the only known substrate for renin, which in the rate limiting enzyme of the renin-angiotensin system. Because the levels of angiotensinogen are close to the Michaelis-Menten constant values for renin, angiotensinogen levels as well as renin levels can control the renin-angiotensin system activity, and thus, up-regulation of angiotensinogen leads to an increase in the angiotensin II. While most circulating angiotensinogen is synthesized in the liver, the kidneys also produce angiotensinogen. Recent studies using experimental animal models have documented that involvement of angiotensinogen in the intrarenal renin-angiotensin system activation and development of hypertension and chronic kidney disease. Enhanced intrarenal angiotensinogen mRNA and/or protein levels were observed in those experimental models, supported the important roles of angiotensinogen in the development and the progression of the disease. Urinary excretion rates of angiotensinogen provide a specific index of the intrarenal renin-angiotensin system status. Using newly developed human angiotensinogen ELISA, we measured urinary angiotensinogen levels in chronic glomerulonephritis patients and patients with type 1 diabetes in childhood. Urinary angiotensinogen level was positively correlated with diastolic blood pressure, urinary albumin, urinary protein levels, and urinary occult blood in chronic glomerulonephritis patients. Furthermore, urinary angiotensinogen level was significantly increased in chronic glomerulonephritis patients not treated with renin-angiotensin system blockers compared with control subjects. Importantly, patients treated with renin-angiotensin blockers had a marked attenuation of this increase. Also, urinary angiotensinogen level was significantly higher in patients with diabetic nephropathy in the pre-micro albuminuric phase than in control subjects. These results suggest that urinary angiotensinogen reflects intrarenal renin-angiotensin system status in chronic glomerulonephritis and may be an early marker of diabetic nephropathy.